Pengaruh Minat Belajar Siswa Terhadap Prestasi Belajar Pada Mata Pelajaran Akuntansi Di Kelas XI SMK Rina Hasanah - Baandaalr Lizein; Susan Susanti; Eko Yudi Setiawan (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose and purpose of this study is to obtain data and want to know how the influence of student interest in learning and to know the influence of student interest in learning on learning achievement in accounting subjects at SMK Rina Hasanah Pandeglang. The method used in this study is case research because in this study data is needed that is in accordance with the existing problem and the purpose of the study, so that analysis and conclusions can be drawn based on the data collected, for that the researcher uses case research. The sample taken was some students at SMK Rina Hasanah Pandeglang the data obtained was in the form of learning interest obtained from the questionnaire while the learning presattion data was taken from the accounting teacher assessment book for one year in the 2021/2022 school year. An overview of students' interest in medium category accounting subjects with a presantase of 62.7%. Likewise, the learning achievement of students in the moderate category with a presantase of 67.8%. From the results of the product moment correlation test, it shows that interest in learning has a positive effect on student learning achievement with a correlation value of 0.35 or has a low relationship. In testing the hypothesis of researchers using the t test formula, then in the proposed hypoiotesis test, namely student interest in learning has a positive and significant influence on learning achievement in accounting subjects at SMK Rina Hasanah Pandeglang received at a 95% confidence level. Meanwhile, the magnitude of the influence of student interest in learning on student learning achievement is 12.25%, meaning that 87.75 is influenced by other factors.